Experimental evaluations of acoustic properties and long-term analysis of a novel indoor living wall. (15th April 2022) - Scamoni, Fabio; Scrosati, Chiara; Depalma, Michele; Barozzi, Benedetta
Abstract: Indoor living walls are important decorative elements that can recreate a natural garden in enclosed spaces. Several aspects are addressed by the scientific literature such as, for instance, classification, the effects on air quality and indoor temperature, greater aesthetic and psychological impact, and improved acoustic treatment of indoor spaces. The main objective of this study is to analyse the acoustic performances of a novel indoor living wall (LW) where plants are rooted in felt layers and grown in hydroponics with no growing medium. The sound absorption of different LW solutions was measured in laboratory (reverberation room). One of them was installed in a Test Building, where sound absorption and sound insulation were measured. The LW has been installed for about two years in the Test Building under controlled conditions of temperature and relative humidity. This gave the unique opportunity to test the sound absorption of the same living wall in the same reverberation room after about two years. The results obtained indicate that the sound absorption performance of the LW is stable, as long as the plants remain in good health. Moreover, an estimation was performed with a calculation model of the reverberation time of the room containing the living wall. Evaluation in real working conditions confirms that indoor living walls can improve the acoustic comfort of indoor spaces by increasing both the sound insulation and the sound absorption area, allowing to reach the optimal reverberation time values provided for by Italian regulations. Graphical abstract: Image 1 Highlights: Innovative living wall reduces sound levels as well as absorbing sound energy. Large leaves perform better than small leaves, exception at highest frequencies. Two years after installation the living wall maintains sound absorption performance. The indoor living wall can improve the acoustic comfort of indoor spaces.